Money, fiscal policy, and interest rates: A critique of Modern Monetary Theory - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
This paper excavates the set of ideas known as modern monetary theory (MMT). The principal conclusion is that the macroeconomics of MMT is a restatement of elementary well-understood Keynesian macroeconomics. There is nothing new in MMT's construction of monetary macroeconomics that warrants the distinct nomenclature of MMT. Moreover, MMT over-simplifies the challenges of attaining non-inflationary full employment by ignoring the dilemmas posed by Phillips curve analysis; the dilemmas associated with maintaining real and financial sector stability; and the dilemmas confronting open economies. Its policy recommendations also rest on over-simplistic analysis that takes little account of political economy difficulties, and its interest rate policy recommendation would likely generate instability. At this time of high unemployment, when too many policymakers are being drawn toward mistaken fiscal austerity, MMT's polemic on behalf of expansionary fiscal policy is useful. However, that does not justify turning a blind eye to MMT's oversimplifications of macroeconomic theory and policy.
Keywords: E00; E02; E10; E12; E24; E40; E58; E62; E63; 330; modern monetary theory; money financed budget deficits; fiscal policy; Zins; Geldtheorie; Haushaltsdefizit; Finanzpolitik; Phillips-Kurve; Keynesianismus